A previously unreported serious adverse event during balloon sinuplasty. (28th January 2013) - Hughes, Nadine; Bewick, Jessica; Van Der Most, Renee; O'Connell, Mike
Abstract : Balloon sinuplasty is considered as a minimally invasive procedure for the treatment of chronic rhinosinusitis. In this case report we describe how a patient undergoing balloon sinuplasty sustained an intraoperative cardiac arrest with no cardiac history. Postoperative investigations were all normal. The patient was discharged on the first postoperative day and further outpatient tests were normal. We postulate that this event occurred due to profound vagal stimulation either on instrumentation of the maxillary mucosa or when the orbit was accidently breached during instrumentation of the right frontal recess. The authors conclude that balloon sinuplasty, despite being minimally invasive surgery, should be performed under the supervision of an anaesthesiologist with the ability of cardiac monitoring and immediate treatment because of possible arrhythmias.